PEMINDAHAN DAN PENJUALAN BARANG WAKAF (Telaah Kritis Fiqih Klasik) - Multazim Ahmadi (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2015)
Supervision of goods endowment is essential, so that the goods waqf maintained condition and still useful. Islamic Shari'a has a privilege compared to previous Shari'a Shari'a where Islamic teachings are universal, integral and global. Islam has set rules about the waqf is perpetual unless revoked by wakif therefore endowments items should not be moved and sold, assigned even passed. And as a revealed religion of Islamic law should be able to balance the needs of the people according to the development and use of certain balance with the principle tasyri. Where Islam is Al-Taisir Wa Al-Takhfif (easy and light) so that development does not cause social turmoil. Goods waqf either moving or not moving, when it is positive to the goods waqf then must be monitored, maintained, and maintained as best as possible, in accordance with the purpose of endowments, may not be sold, and assigned, but if the goods waqf is damaged, does not fulfill its function as waqf property, can not be utilized, it is the waqf property be sold and the money to buy other goods instead, can even be transformed to enable the more benefits and maslahah. Move items endowments from one place to another because of damage, can not function or be less strategic legal provisions do not change the name of waqf, not eliminate, and contains more benefits and goodness.